CT angiography versus clinical, echocardiographic, and invasive gradients in coarctation and recoarctation of the aorta - André Vaz; Ludmila M. Young; Renata Muller Couto; Kevin R. M. de Paula; Eduardo K. U. N. Fonseca (Annals of Pediatric Cardiology)
Background: Aortic coarctation is a congenital heart disease characterized by narrowing of the distal aortic arch or isthmus. Its management relies on arterial hypertension, stenosis severity, and peak-to-peak gradients. Despite various assessment methods, there is limited discussion on measuring stenosis using computed tomography (CT) angiography and its correlation with clinical, echocardiographic, and invasive gradients, as well as surgical or endovascular indications. Materials and Methods: This retrospective study included 129 patients with aortic coarctation or recoarctation who underwent clinical, echocardiographic, catheterization, and CT angiography. Patients with mid-arch hypoplasia and patent ductus arteriosus were excluded from the study. CT angiography was used, and detailed measurements of the aortic isthmus and diaphragmatic aorta were performed, including isthmus-to-diaphragm ratios, body surface area-indexed measurements, and z-scores. Results: Multiple parameters presented moderate-to-high correlation with echocardiographic and invasive gradients. The best discriminator for significant invasive gradient (>20 mmHg) was the hydraulic diameter Pediatric Heart Network z-score (area under the receiver operating characteristic curve = 0.869), and the best predictor for intervention was the minimum diameter Detroit z-score (P < 0.001). The isthmus-to-diaphragm area ratio presented good diagnostic accuracy (area under the receiver operating characteristic curve = 0.814), with an optimal cutoff of 0.73 for a significant invasive gradient. Interobserver reliability was high (>0.9) for all measurements. Conclusion: CT angiography-derived isthmus-to-diaphragmatic area ratio is a simple, accurate, and reliable assessment of aortic coarctation and recoarctation severity. These findings support its use in clinical decision-making and suggest potential for standardized protocols.